Virus-induced gene silencing: empowering genetics in non-model organisms. (19th November 2018) - Dommes, Anna B; Gross, Thomas; Herbert, Denise B; Kivivirta, Kimmo I; Becker, Annette
Abstract : We summarize the main contributions to plant science of virus-induced gene silencing-based research in non-model plants, and provide guidelines on best practice when carrying out such experiments. Abstract: Virus-induced gene silencing (VIGS) is an RNA interference-based technology used to transiently knock down target gene expression by utilizing modified plant viral genomes. VIGS can be adapted to many angiosperm species that cover large phylogenetic distances, allowing the analysis of gene functions in species that are not amenable to stable genetic transformation. With a vast amount of sequence information already available and even more likely to become available in the future, VIGS provides a means to analyze the functions of candidate genes identified in large genomic or transcriptomic screens. Here, we provide a comprehensive overview of target species and VIGS vector systems, assess recent key publications in the field, and explain how plant viruses are modified to serve as VIGS vectors. As many reports on the VIGS technique are being published, we also propose minimal reporting guidelines for carrying out these experiments, with the aim of increasing comparability between experiments. Finally, we propose methods for the statistical evaluation of phenotypic results obtained with VIGS-treated plants, as analysis is challenging due to the predominantly transient nature of the silencing effect.